Implications of on farm research for local knowledge related to fruits flies and the weaver ant Oecophylla longinoda in mango production - Sinzogan, A.A.C.; Mele, P. van; Vayssières, Jean-François (Informa UK Limited, 2008)
We interviewed half of the mango-growers in northern Benin, including 15 farmers involved in a regional fruit fly project, and held focus group discussions with women fruit-pickers. They were asked about pest management and their knowledge of a weaver ant, Oecophylla longinoda. All considered low yields due to fruit flies to be the principal constraint upon mango production, estimating economic losses to be between 20 and 45%. None could recognize damage during the first 2 days after fruit fly egg deposition. On-farm research persuaded farmers to stop using insecticides and it also changed negative perceptions of Oecophylla. Over 80% of the farmers involved in on-farm research, compared to 25% of those not involved, reported Oecophylla to be beneficial. All fruit-pickers knew that ants protected mango from fruit flies, with 60% attributing better mango quality in terms of appearance, shelf-life and sweetness to the presence of Oecophylla. Nevertheless, 40% of the pickers still considered weaver ants a nuisance pest during harvest. Ways of reducing this nuisance need to be developed for Oecophylla to gain wider acceptance by mango-growers.